2019
DOI: 10.1111/iej.13105
|View full text |Cite
|
Sign up to set email alerts
|

Influence of nanostructured calcium aluminate and calcium silicate on the liver: histological and unbiased stereological analysis

Abstract: Aim To examine the potential systemic toxicity of nanostructured materials based on calcium silicate and calcium aluminate, for potential application in Dentistry. Methodology Twenty‐four Albino Wistar rats aged 2 months were used as an in vivo animal model for subcutaneous implantation of the investigated materials, placed in polyethylene tubes. Thirty days after implantation, the livers of the rats were analysed and following histological and stereological parameters were evaluated for volume density of hepa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 35 publications
(68 reference statements)
1
12
0
2
Order By: Relevance
“…It was concluded that materials induced normal and reversible response in the liver. Namely, the proliferation of parenchymal cells in this case was also reported, with no visible signs of pathological changes or immunological reaction to the materials [32].…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…It was concluded that materials induced normal and reversible response in the liver. Namely, the proliferation of parenchymal cells in this case was also reported, with no visible signs of pathological changes or immunological reaction to the materials [32].…”
Section: Discussionsupporting
confidence: 61%
“…In our previous study, the effect of calcium silicate and calcium aluminate implantation on systematic subchronic toxicity was evaluated [32]. It was concluded that materials induced normal and reversible response in the liver.…”
Section: Discussionmentioning
confidence: 99%
“…Also, an experimental CS-HAP cement implanted subcutaneously in rats has induced a low inflammatory reaction of the tissue over the same period of time, which was lower than that of ProRoot MTA [81]. In addition, a nanostructured CS mixture did not show any negative effect on liver in rats after thirty days of oral administration [82]. Pulp capping in this animal model revealed statistically significantly lower inflammatory reaction of CS samples, in comparison to the Super-EBA (Keystone Ind., Muerstown, Pensilvania, USA) and ProRoot MTA.…”
Section: Biological Properties Of Cs Cementsmentioning
confidence: 88%
“…The results showed that using materials induced normal and reversible response in the liver. Namely, investigated proliferation rate with the average number of immunoreactive Ki67 positive parenchymal cells was also reported, with no visible signs of pathological changes or immunological reaction to the materials [ 42 ].…”
Section: Discussionmentioning
confidence: 99%